Natural Deduction System for the Logic of Binary Relations Based on the Algebraic Tradition - Cerioli, Márcia Rosana; Suguitani, Leandro Oliva; Viana, Jorge Petrúcio (Anais do Workshop Brasileiro de Lógica (WBL), 2020)
We present a proper natural deduction system (ND-system) for a logic of binary relations based on the algebraic tradition. Our system is an evolution from [W. W. Wadge. TCR 5, The University of Warwick, 1975]. We point out some aspects where Wadge's formalism fails as an ND-system and fix them all.